2016
DOI: 10.1007/s11239-016-1362-3
|View full text |Cite
|
Sign up to set email alerts
|

Ten years of cerebral venous thrombosis: male gender and myeloproliferative neoplasm is associated with thrombotic recurrence in unprovoked events

Abstract: Cerebral venous thrombosis (CVT) is a rare venous thrombotic event. We review our local experience in the management of CVT in comparison to other venous thromboembolism (VTE) with specific focus on risk factors for thrombotic recurrence. Retrospective evaluation of consecutive CVT presentations from January 2005 to June 2015, at two major tertiary hospitals in Northeast Melbourne, Australia. This population was compared to a separate audit of 1003 consecutive patients with DVT and PE. Fifty-two patients (30 f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…8 There is a lack of data evaluating the risk of CVT recurrence, as well as whether the risk factors for CVT are similar to those for DVT and PE. One recent study has found that after a 10-year follow-up on patients with DVT and PE only 5.2% developed CVT, 9 while for patients with CVT only 5.8% developed DVT/PE later on. 10 Therefore, no significant link between CVT and DVT/PE has been found so far.…”
Section: Cvt Commonly Affects Youngmentioning
confidence: 99%
“…8 There is a lack of data evaluating the risk of CVT recurrence, as well as whether the risk factors for CVT are similar to those for DVT and PE. One recent study has found that after a 10-year follow-up on patients with DVT and PE only 5.2% developed CVT, 9 while for patients with CVT only 5.8% developed DVT/PE later on. 10 Therefore, no significant link between CVT and DVT/PE has been found so far.…”
Section: Cvt Commonly Affects Youngmentioning
confidence: 99%
“…49 In adults, risk factors for recurrence of CVT are male gender, myeloproliferative diseases (polycythemia vera or essential thrombocythemia), prior venous thrombotic events, and severe thrombophilia. [50][51][52] Oral anticoagulation after the acute phase of CVT contributes to the prevention of further venous thrombotic events, including recurrence of CVT. However, there have been no randomized controlled trials or prospective controlled studies assessing optimal duration of oral anticoagulation in this setting.…”
Section: Long-term Managementmentioning
confidence: 99%